Hospitalization due to conditions sensitive to primary care and expansion of the Family Health Program in Brazil: an ecological study - Roger Flores Ceccon; Stela Nazareth Meneghel; Paulo Ricardo Nazário Viecili (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2014)
OBJECTIVE: To evaluate the relationship between hospitalization due to conditions that are sensitive to primary care and the population coverage by the Family Health Strategy (ESF) Units of the Brazilian Federation Units in the last decade. METHODS: This is an ecological study that investigated preventable hospitalizations and coverage of primary health care in Brazil in the historic series from 1998 to 2006. Statistical analysis was performed using the Pearson correlation test and simple linear regression. RESULTS: In the studied period, we found an association between population coverage and reduced ESF admissions for primary care sensitive conditions in Brazil (β = -28.78, p ≤ 0.01), which occurred in 38.4% of the Federation Units. CONCLUSION: There was a positive relationship between the expansion of ESF coverage and a decline in hospitalizations for ACSC in the country. The findings of this study help to evaluate the ESF and primary care in Brazil.